2005
DOI: 10.1242/dev.01618
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid signaling controls cortical actin assembly and cytoarchitecture in Xenopus embryos

Abstract: The mechanisms that control shape and rigidity of early embryos are not well understood, and yet are required for all embryonic processes to take place. In the Xenopus blastula, the cortical actin network in each blastomere is required for the maintenance of overall embryonic shape and rigidity. However, the mechanism whereby each cell assembles the appropriate pattern and number of actin filament bundles is not known. The existence of a similar network in each blastomere suggests two possibilities: cellautono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
5
26
0
Order By: Relevance
“…LPA expression suggests housekeeping functions in Xenopus LPA1 and LPA2 have already been cloned in Xenopus (Kimura et al 2001;Lloyd et al 2005). Our results indicate a wider distribution for LPA1.1 and LPA1.2 in adult frog than previously published, but confirm that these transcripts are strongly expressed in the nervous system and ovary (oocytes) (Kimura et al 2001).…”
Section: Expression Of S1p Genes Suggests Specific Roles In Xenopussupporting
confidence: 76%
See 3 more Smart Citations
“…LPA expression suggests housekeeping functions in Xenopus LPA1 and LPA2 have already been cloned in Xenopus (Kimura et al 2001;Lloyd et al 2005). Our results indicate a wider distribution for LPA1.1 and LPA1.2 in adult frog than previously published, but confirm that these transcripts are strongly expressed in the nervous system and ovary (oocytes) (Kimura et al 2001).…”
Section: Expression Of S1p Genes Suggests Specific Roles In Xenopussupporting
confidence: 76%
“…Although the sequences for several LPA/S1P receptors were available in databases, we cloned cDNAs for 8 of these receptors by in silico analysis, due to the increased coverage of ESTs and the X. tropicalis genomic DNA sequencing projects. In particular we identified sequences for X. tropicalis LPA3 and S1P3 that previous studies failed to identify (Lloyd et al 2005;Ohuchi et al 2008). Bioinformatics analysis indicated that all the sequences display the characteristic extracellular N terminus and the 7 transmembrane domains (TM) of these receptors which are located at the same position to the human orthologous sequences.…”
Section: Evolutionary Conserved Members Of the Lpa And S1p Families Amentioning
confidence: 96%
See 2 more Smart Citations
“…Cells that are dividing in vivo, or dissociated in calcium-and magnesium-free saline, or depleted of C-cadherin, all lose their dense cortical actin network, but retain a sparse network, even in the absence of cadherin on the cell surface (Fig. 2) (see also Lloyd et al, 2005). This sparse network is clearly cadherin-independent and is independent of the dense network.…”
Section: Research Articlementioning
confidence: 95%